The Use Behavior of Tracking and Tracing Services in E-Commerce Logistics - Kinda Rizki Widianti; Eko Ruddy Cahyadi; Alim Setiawan Slamet (IPB University, 2021)
An increasing business transaction can cause rapid growth in online shops and marketplace. One of the affected is an online shop. From several logistic services, tracking and tracing information services are the main focus in this study because online shops as the business partner have a lack of attention in these services. The objective of this study is to investigate the factors of online shop behavior in using tracking and tracing information services.This study used a unified theory of acceptance and use of technology (UTAUT) as the framework. The quantitative data were collected through questionnaires from 207 samples of online shops selling women’s fashion and listed in the marketplace. Data were analyzed using structural equation modeling (SEM) with LISREL 8.70.The result of this study found that “the intention to use” the tracking and tracing information services depend on the effort expectancy (EE) dan social influence (SI), while “user behavior” depends on facilitating condition (FC) and the intention to use. The ease of access factor and learning the tracking and tracing information services are the important factors for the intention to use, whereas electronic devices and internet network factors used by the online shops are the main factors for the user behavior. Logistics companies need to provide information services that can help the online shops in controlling their goods in a good way where the ease of access and learning become the main focus that needs attention. Furthermore, online shops need to facilitate their admins with technological devices and a good internet network to make the admins easy to access information services.